Slalom technique for multilevel degenerative spinal stenosis, surgical outcome and complication rate: review of our experience - Ghazwan Abdullah Hasan; Hayder Qatran Raheem; Khan, Shahbaz; Yasameen Bani Wais; Ahmed Alqatub; Mustafa Katran (Journal of the Pakistan Medical Association, 2024)
Lumbar canal stenosis (LCS) is a common spinal disease affecting the elderly. Primarily it is asymptomatic until there is neurogenic claudication. Minimally invasive surgical (MIS) techniques are used to treat patients with lumbar spinal stenosis (LSS), while tubular system with alternative multilevel decompression is specifically used for those with minimal back pain and no mechanical instability on dynamic imaging. The aim of the study is to evaluate surgical outcome of Slalom procedure and complications in Middle East population. One hundred and five patients with lumbar stenosis (61 males and 44 females) underwent the procedure between 2015-2021 who were regularly followed-up using preoperative and postoperative COMI score (the core outcome measure index) at six months after index surgery. Progressive improvement in COMI score from average seven pre-op score to an average of three after six months of index surgery. —Continue